The Journey of knowledge. How knowledge is managed in a multi scale organization: Example of a socio-professional integration project in a French association - Napaseuth, Marlina (Cadernos IS-UP, 2025)
This paper examines the relationships between the different actors (social and vocational integration counsellors, trainers, educational engineers and project managers) at different levels of the organisation through the prism of knowledge needs. Via a socio-professional integration project, this paper analyses this impact of knowledge in a complex multiscale organization of a French association. This paper will tell the story of knowledge management in this project. We will focus on the role of each actor and the relationship between them. How does the knowledge pass between different scales of the organisation and different cities? Have they experienced some loss of knowledge with the change in geographical and organisational scale? How do they manage the knowledge and data they already have and how do they manage the new knowledge they create in this project? What method? What tool? And who? We propose to follow the path of knowledge in this project.